Electoral Systems and the Influence of the Median Voter: Quasi-Experimental Evidence from popular and parliamentary votes - Marco Portmann; Reiner Eichenberger; David Stadelmann (Verein für Socialpolitik, 2010)
When moving from a plurality rule to a proportional system, members of national parliament have more incentives to diverge from the median voter's preferences. We match voting behavior concerning legislative proposals of Swiss members of parliament with real referenda outcomes on the same issues for the years 1996 to 2009. This quasi-experimental data allows us to identify whether differences in electoral systems induce members of parliament to diverge from the choices of the median voter. Empirical results indicate that members of parliament from districts with proportional representation tend to diverge significantly more from the median voter's preferences than members of parliament from districts with plurality rule.
Keywords: D72; H00; D70; 330; Median Voter; Electoral Systems; Political Economy